Veniamin Mikhailovich Samosudov — man and scientist at crossroads of times (1926–2010) - S. V. Novikov (Омский научный вестник: Серия "Общество. История. Современность")
In the 1960’s–1970’s, the development of regional historical science took place, which reflected the General trend for the country. During this period, changes were made to the concept of the development of socialist society, which caused the transition to universal secondary education. This transition required the training of teachers of history and social Sciences, which was entrusted to pedagogical institutes. The result was changes in the content of training of scientific and pedagogical personnel in the region. During these years, Samosudov's scientific and managerial career developed. Based on the memoirs of colleagues, materials of archival collections, personal impressions, the author comes to the conclusion that the doctor of historical Sciences, Professor, member of the CPSU, rector of the OSPI named after M. Gorky was a major historian — the Creator of the scientific school. He was a man of his time: a witness to the socialist transformation of the village, a participant in the war, an organizer of education in the region. About how his attitude to society changed during the transformations in the state, reports the test of the presented article